PROJECT BASED LEARNING BERSUMBER BELAJAR POTENSI LINGKUNGAN LOKAL TERHADAP PEMAHAMAN KONSEP, KETERAMPILAN ILMIAH, DAN SIKAP ILMIAH SISWA - Kholishotul Fuadah; Murni Saptasari; Ibrohim Ibrohim (Universitas Negeri Malang, 2016)
The 2013 curriculum is designed to develop attitude, knowledge, and skills competencies. Students' low scientific and attitudes skills lead to low concept comprehension. The aim of this research was to determine the effect of Project Based Learning used local potential of environment as learning resource towards the students' concept comprehension, scientific skills, and scientific attitude. The type of this research was quantitative descriptive with pretest-posttest control group design design. Data was collected by tests and observations. The result of the research showed that Project Based used local potential of environment as learning resource had a positive effect on the students' concept comprehension, scientific skills, and scientific attitude.